Women, Peace, and Conflict; Increasing The Capability and Number of Indonesian Women Peacekeepers in the United Nations Interim Force in Lebanon (UNIFIL) - Masyrofah Masyrofah; Amany Lubis (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2022)
This article analyses increasing the capability and number of Indonesian women's participation in the UNIFIL (United Nations Interim Force in Lebanon) and the approaches and strategies women peacekeepers used while on duty at UNIFIL. Based on Presidential Regulation No. 18/2014 concerning the protection and empowerment of women and children in social conflicts, in contrast to the fact that women's involvement in carrying out UNIFIL's peacekeeping mission is still weak, even though women have great potential in soft power. Women have different approaches to seeking peace between the two parties involved in the conflict or keeping the peace from disappearing. This research is qualitative with a statutory approach, peacebuilding, conflict resolution, international law, and politics—data collection techniques through interviews and literature studies. These study findings are evidence of Indonesia's success in world peace missions. Women peacekeepers in the Indonesian National Armed Forces have a role that cannot be replaced by other elements, considering the conflict field prioritizes the unique skills of the Women's Indonesian National Armed Forces and Women's Police. Apart from that, the unique socio-religious-cultural characteristics in the South Lebanese Region have a reasonably complex composition, including interfaith and intra-faith sensitivity, Sunni-Shi'a dimensions, and the Druze sect. The readiness of Indonesian women peacekeepers is in good condition and continues to increase the skill and strategy to keep peace worldwide. The potential of Indonesian women peacekeepers is an integral part of the Indonesian National Armed Force's mission. Namely, the ability for territorial development is a distinctive characteristic of the Indonesian National Armed Forces as a national army born in conditions of struggle. Its operational capabilities are closely related to raising support from the community in its area of operation.